MACARONS SUBSTITUTION WITH BLACK GLUTINOUS FLOUR (MACETAM) AS AN INNOVATION DESSERT PRODUCT - Minta Harsana, Florentin Verena Tjandra (Prosiding Pendidikan Teknik Boga Busana, 2020)
This final project aims to find the right recipe on a product Macarons Substitution With Black Glutinous Flour (macetam), know the content of the nutritional value and recognize Macarons Substitution With Black Glutinous Flour (macetam). The type of research used is a Research and Development (R & D), by using the 4D model development approach that Define, Design, Develop and Desseminate. With a standard product recipe determination procedures, validation and revision, test A limited scale and large scale hedonic test (exhibit). The place and time of the Laboratory of Culinary Research, Culinary and Clothing Engineering Department, Faculty of Engineering, Yogyakarta State University, conducted from January to May 2019. The test material is in the form of samples from each product and a panelist form. The results obtained from the research of this product are: 1) the right recipe on a macetam product that is 40% black glutinous flour and almond flour 60%. 2) The content of the nutritional value Macetam includes water, ash, protein, fat, crude fiber, carbohydrates and energy. 3) Community acceptance of Macarons products overall average of 3.72 which indicates that the product can be accepted by the public. Keywords: Black glutinous flour, Macarons